2015
DOI: 10.1111/ppc.12105
|View full text |Cite
|
Sign up to set email alerts
|

Are Different Coping Styles Mitigating Perceived Stress Associated With Depressive Symptoms Among Pregnant Women?

Abstract: Health services should dedicate resources to teach women positive coping styles to decrease their vulnerability to developing antenatal depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
2
8
0
1
Order By: Relevance
“…In line with prior research in pre-COVID pregnancy samples (e.g., Guardino and Dunkel Schetter 2014 ; Lau et al 2016 ), we found that dysfunctional coping was related to elevated mental health problems, emotion-focused coping was associated with less mental health problems, whereas problem-focused coping was not related to mental health. These findings add to the larger literature showing that specific coping strategies are associated with better/worse mental health outcomes during the COVID-19 pandemic (Jiang et al 2020 ; Jungmann and Witthöft 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with prior research in pre-COVID pregnancy samples (e.g., Guardino and Dunkel Schetter 2014 ; Lau et al 2016 ), we found that dysfunctional coping was related to elevated mental health problems, emotion-focused coping was associated with less mental health problems, whereas problem-focused coping was not related to mental health. These findings add to the larger literature showing that specific coping strategies are associated with better/worse mental health outcomes during the COVID-19 pandemic (Jiang et al 2020 ; Jungmann and Witthöft 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Research has distinguished between three major types of coping: (1) problem-focused coping, which involves actions aimed at addressing the problem (e.g., planning, seeking instrumental support), (2) emotion-focused coping, which aims to manage negative emotions (e.g., seeking emotional support, cognitive restructuring), and (3) dysfunctional coping, which involves maladaptive strategies that are not helpful in dealing with the stressor (e.g., denial, behavioral disengagement) (Carver 1997 ; Folkman and Moskowitz 2004 ). Indeed, dysfunctional coping has been associated with adverse mental health outcomes in pregnant women across different circumstances (Chen et al 2020 ; Guardino and Dunkel Schetter 2014 ; Gutiérrez-Zotes et al 2015 ; Lau et al 2016 ). In contrast, the effects of problem-focused and emotion-focused coping are mixed, though these strategies tend to be associated with more positive outcomes in pregnant women (Guardino and Dunkel Schetter 2014 for review).…”
Section: Introductionmentioning
confidence: 99%
“…Coping refers to the individual cognitive and behavioral strategies to master, reduce or tolerate the internal and external demands of stressful situations [25]. These coping strategies may be positive or negative [26]. Positive coping is an active coping style that focuses on taking constructive actions and changing the stressful situation, and it is typically associated with problem-solving behavior and effective emotion regulation [27].…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, teaching positive confrontation can minimize the manifestation of these events. 14 Conclusions the prevalence of depressive symptoms among pregnant women is of 15.47%, and emotional violence is the main factor associated with gestational depression.…”
Section: Introductionmentioning
confidence: 99%